2015
DOI: 10.1021/jacs.5b08103
|View full text |Cite
|
Sign up to set email alerts
|

Ni-Catalyzed Borylation of Aryl Fluorides via C–F Cleavage

Abstract: A Ni-catalyzed borylation via C-F activation is described. This protocol is distinguished by a wide scope, including unactivated fluoroarenes, without compromising its efficiency and scalability, thus representing a significant step-forward towards the implementation of C-F activation protocols.Metal-catalyzed cross-coupling reactions of organic halides have become indispensable tools in modern synthetic chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
103
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 220 publications
(108 citation statements)
references
References 77 publications
3
103
1
1
Order By: Relevance
“…Interestingly,n either isomers originating from alkene chain-walking isomerization nor exo-cyclized products were observed. We rationalized that abulky NHC on Ni could both accelerate the reductive elimination step to avoid isomerization and favor the endo-cyclization pathway for steric reasons.R emarkably,a lthough structurally similar NHC-stabilized Ni 0 complexes were reported to activate CÀ Fb onds over CÀHb onds in polyfluoroarenes, [15,16] no CÀF bonds cleavage was observed in the current system. We reasoned that our bulky NHC favors the formation of active monomeric Ni/NHC catalyst [22b] thus facilitating C À Hb ond activation instead.…”
mentioning
confidence: 62%
See 3 more Smart Citations
“…Interestingly,n either isomers originating from alkene chain-walking isomerization nor exo-cyclized products were observed. We rationalized that abulky NHC on Ni could both accelerate the reductive elimination step to avoid isomerization and favor the endo-cyclization pathway for steric reasons.R emarkably,a lthough structurally similar NHC-stabilized Ni 0 complexes were reported to activate CÀ Fb onds over CÀHb onds in polyfluoroarenes, [15,16] no CÀF bonds cleavage was observed in the current system. We reasoned that our bulky NHC favors the formation of active monomeric Ni/NHC catalyst [22b] thus facilitating C À Hb ond activation instead.…”
mentioning
confidence: 62%
“…[8] Ty pically,t etralin systems are synthesized through Friedel-Crafts type cyclization of aryl derivatives [9] or hydrogenation of naphthalene derivatives. [14] Second, selective activation of CÀHbonds over multiple CÀFb onds are required, although experimental [15] and computational [16] studies have suggested that Ni 0 complex exclusively favor oxidative addition into CÀFbonds instead of C À Hb onds in polyfluoroarenes. To our knowledge,t here are no general catalytic methods for the asymmetric synthesis of unfunctionalized fluorotetralins.Inthis context, we surmised that aN i-catalyzed asymmetric C À Ha lkylation of easily available alkene tethered fluoroarenes by an intramolecular hydroarylation might provide an efficient construction of chiral fluorotetralin derivatives (Scheme 1C).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Zuschriften coupling with vinyl fluorides is slow at ambient temperatures, [15,16] it is suggested that the product formation occurs via 1,2-elimination of the corresponding alkyl-[Ni]-complex. [17] With respect to the mechanistic proposal for the reaction in toluene,i tw as observed that use of a-methyl styrene (72)l ed to products resulting from aH eck-type reaction (74)and hydroarylation (75).…”
Section: Angewandte Chemiementioning
confidence: 99%